Response to radiation in tumor biopsies from colorectal cancer patients. - Burgos-Molina, Antonio Manuel; Rodríguez-García, Marta; González-Vidal, Alejandro; Mercado-Sáenz, Silvia; Ruiz-Gómez, Miguel José (My University, 2024)
Analysis of the response to radiation of tumor biopsies can provide very valuable information about the possible resistance of colorectal cancer to treatment. Resistance mechanisms involve overexpression of the CREB-KDM4B-STAT3 axis, as well as alterations in the expression of BEX1 and BTG3. It is important to highlight the increase in DNA repair and decrease in apoptosis by RAD50 and IGF-1R. New therapies based on the use of molecular response markers and new therapeutic targets that address radiation resistance would be very useful for the individualization of treatments and precision medicine.
Keywords: Cáncer - Prevención; Cáncer colorrectal; Biopsia; Immune system